Knowledge construction in the community of fishing women in the region of Guaraqueçaba – PR - Elaine Mandelli Arns; Faimara do Rocio Strauhs (Liinc em Revista)
In the knowledge dynamics, women's craft communities form a great ba: knowledge-sharing space. The objective of this article is to establish the dynamics of the process of knowledge construction and professional belonging in the Community of Practice of professional artisanal fisherwomen, in the region of Guaraqueçaba – PR – Brazil – in the light of the Actor-Network Theory, with an approximative approach to the SECI MODEL, a classic in the field of Knowledge Management. Applied, exploratory-descriptive and explanatory research was used as a methodology, with observant participation and mixed methods in the treatment of data, favoring the life stories, communal interactions and day-to-day activities of the involved fisherwomen. Findings: The network of human and non-human elements, the process of knowledge creation, was mapped establishing a comparison between the model proposed in this community and the SECI Model. It was confirmed that the SECI Model also applies outside formal organizations. In the analysis of communities of practice, the concept of communities of practice was expanded, in this context, to a community of women's craft. Research limitations: The shyness of the fisherwomen, the rainy weather not allowing for research or fieldwork, the slow pace of time on the way life passes in those communities; all these, require an adaptation from outsiders